Identifying new concepts for innovative lighting-based interventions to influence movement and behaviours in train stations. (December 2020) - Hughes, N; Ryan, B; Hallewell, M; Coad, N; Grant, A; Parrott, N; Roberts, S; Thompson, K
The disorderly and disrupted movement of passengers within train stations are key concerns in rail transport, especially where there are increasing numbers of passengers, coupled with often out-dated, adapted station spaces. With careful planning and design, different characteristics of lighting can be employed to address problems relating to the movement and behaviour of passengers in railway environments. This study aims to offer an approach to identify new concepts for lighting-based interventions to influence passenger movement behaviours within train stations. Behaviourally orientated lighting literature was reviewed, providing the knowledge base to inform a series of engagement activities with transport stakeholders and lighting technologists, to understand problematic behaviours and how these might be resolved through targeted lighting design. In combining findings from the literature with insights from rail and transport-related industry stakeholders and lighting specialists, a number of potential opportunities for novel applications of lighting have been identified. Six scenarios are developed that illustrate these opportunities for potential lighting-based interventions to influence train passenger movement and behaviour. These scenarios can be used to inform the direction of further research and consideration of how different lighting characteristics can affect rail passenger behaviours.